Facteurs socioéconomiques et décrochage des études au premier cycle universitaire - Alex Romeo SUEBANG; Daouda MAINGARI (Éducation et Socialisation)
The issue of dropping out of school in Cameroon has so far only focused on primary and secondary education (Ngoufo Yemedi, 2004; Noumba, 2008; Ntouda Betsogo, 2011). This study examines the factors that may be related to dropping out of university studies in the country. Its objective is therefore to examine the link between socioeconomic factors and dropping out of studies in the first cycle of FALSH at the University of Yaounde I. The study is based on a quantitative research estimate calling for the questionnaire as a data collection instrument. The results obtained were interpreted on the basis of the social theory of Baudelot and Establet (1971) and Mballa Owono (1986) and the economic theory of human capital of Becker (1964). These results show the existence of a relationship between three factors (father's level of education, socio-professional level of the father, time spent by the student in a paid job during studies per week) and dropping out of undergraduate studies of FALSH at the University of Yaounde I.